2018
DOI: 10.1159/000489645
|View full text |Cite
|
Sign up to set email alerts
|

A Tick Cysteine Protease Inhibitor RHcyst-1 Exhibits Antitumor Potential

Abstract: Background/Aims: We previously identified a potent and tight-binding inhibitor of cysteine proteases from Rhipicephalus haemaphysaloides, RHcyst-1, which belongs to the cystatin type 1 family. Cathepsins, which are members of the cysteine protease family, participate in various pathological processes, including the initiation and development of cancers. The present study aimed to investigate the antitumor effects of RHcyst-1 and to explore the underlying mechanism of these effects. Methods: Different tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In our previous study, we reported that RHcyst-1 belongs to the type1 cystatin family and is involved in tick physiology [13]. In this study, although RHcyst-1 was not directly detectable in serum from rabbits on which ticks had repeatedly fed (Additional file 1: Figure S1), previous studies have shown that RHcyst-1 has a broad spectrum of mammalian cathepsin-inhibition activities and mediates specific immune responses in tumor-bearing mice [13, 18]. Recently, exosomes have been most extensively studied and tick-derived exosomes were reported to mediate transmission of tick-borne disease [2932].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In our previous study, we reported that RHcyst-1 belongs to the type1 cystatin family and is involved in tick physiology [13]. In this study, although RHcyst-1 was not directly detectable in serum from rabbits on which ticks had repeatedly fed (Additional file 1: Figure S1), previous studies have shown that RHcyst-1 has a broad spectrum of mammalian cathepsin-inhibition activities and mediates specific immune responses in tumor-bearing mice [13, 18]. Recently, exosomes have been most extensively studied and tick-derived exosomes were reported to mediate transmission of tick-borne disease [2932].…”
Section: Discussionmentioning
confidence: 79%
“…In addition, the safety of RHcyst-1 on the normal cell lines 293T, Vero and CHO has been evaluated in our previous studies. RHcyst-1 treatment did not change the activity of normal cells and did not induce apoptosis in these cell lines [18]. These results show that the suppression of BMDC differentiation by RHcyst-1 is not due to apoptosis or cytotoxicity.…”
Section: Resultsmentioning
confidence: 86%
“…Our ndings, however, go beyond the prior. A powerful and tightly-binding inhibitor of cysteine proteases, RHcyst-1, belonging to type 1 cystatins, was discovered in Rhipicephalus haemaphysaloides (Acari, Ixodidae) saliva and demonstrated anticancer potential in another work by Wei et al (2018). Four distinct tumor cell types, including the human cervical (HeLa), lung (A549), and ovarian (SKOV-3) cancer cell lines, as well as the murine melanoma B16-F10 cell lines, are strongly inhibited in vitro by RHcyst-1 in terms of proliferation, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators attributed their results to the effects of RhCyst-1 in decreasing the number of myeloidderived suppressor cells (MDSCs) from the peripheral blood mononuclear cells (PBMCs). However, the investigators recommended further studies to discover the link between RhCyst-1 and MDSCs regulation from the spleens and PBMCs (60) .…”
Section: Ticksmentioning
confidence: 99%